Field mixtures of currently used pesticides in agricultural soil pose a risk to soil invertebrates. (15th July 2022) - Panico, Speranza C.; van Gestel, Cornelis A.M.; Verweij, Rudo A.; Rault, Magali; Bertrand, Colette; Menacho Barriga, Carlos A.; Coeurdassier, Michaël; Fritsch, Clémentine; Gimbert, Frédéric; Pelosi, Céline
Abstract: Massive use of pesticides in conventional agriculture leads to accumulation in soil of complex mixtures, triggering questions about their potential ecotoxicological risk. This study assessed cropland soils containing pesticide mixtures sampled from conventional and organic farming systems at La Cage and Mons, France. The conventional agricultural field soils contained more pesticide residues (11 and 17 versus 3 and 11, respectively) and at higher concentrations than soils from organic fields (mean 6.6 and 10.5 versus 0.2 and 0.6 μg kg −1, respectively), including systemic insecticides belonging to neonicotinoids, carbamate herbicides and broad-spectrum fungicides mostly from the azole family. A risk quotient (RQi ) approach evaluated the toxicity of the pesticide mixtures in soil, assuming concentration addition. Based on measured concentrations, both conventional agricultural soils posed high risks to soil invertebrates, especially due to the presence of epoxiconazole and imidacloprid, whereas soils under organic farming showed negligible to medium risk. To confirm the outcome of the risk assessment, toxicity of the soils was determined in bioassays following standardized test guidelines with seven representative non-target invertebrates: earthworms ( Eisenia andrei, Lumbricus rubellus, Aporrectodea caliginosa ), enchytraeids ( Enchytraeus crypticus ), Collembola ( Folsomia candida ), oribatid mites ( Oppia nitens ), and snails ( Cantareus aspersus ). Collembola and enchytraeid survival and reproduction and land snail growth were significantly lower in soils from conventional compared to organic agriculture. The earthworms displayed different responses: L. rubellus showed higher mortality on soils from conventional agriculture and large body mass loss in all field soils, E. andrei showed considerable mass loss and strongly reduced reproduction, and A. caliginosa showed significantly reduced acetylcholinesterase activity in soils from conventional agriculture. The oribatid mites did not show consistent differences between organic and conventional farming soils. These results highlight that conventional agricultural practices pose a high risk for soil invertebrates and may threaten soil functionality, likely due to additive or synergistic "cocktail effects". Graphical abstract: Image 1 Highlights: soils from conventional farming contained more pesticides than organic farming soils. conventional soils pose a high risk to soil invertebrates based on risk quotients. soils under organic farming showed a negligible to medium risk. conventional soils did show toxicity in bioassays with several soil invertebrates. additive or synergistic "cocktail effects" of mixtures might explain the toxicity.